Pull and Push Factors of Students’ Enrolment in the TVET Programme at Community College in Malaysia - Abdul Aziz, Shahrun Nizam Bin; Zulkifli, Normala binti; Mat Nashir, Irdayanti binti; Abdul Karim, Noor Al-Huda binti (Journal of Technical Education and Training, 2019)
Malaysia aims to achieve a high-income economy by 2020. Hence, a highly skilled workforce is essential to achieving this goal through enhancement of its TVET graduates. This study is aimed at identifying the pull and push factors affecting student enrolment in the TVET programme at community colleges in Malaysia. This study employed a questionnaire to collect data. A total of 377 students from 11 community colleges in peninsular Malaysia were randomly selected as study sample. In this study, the mean score was used to determine the tendency of factors that influence student enrolment, while the Mann-Whitney U test was used to measure the difference in the mean score of the main factor. The findings show that all push and pull factors significantly influence student enrolment in TVET institutions. The study highlighted career prospect as the main pull factor, while the main push factors comprise students’ interest. The findings also show that there is a significant difference in the mean score of these two factors based on ethnicity. Therefore, students’ interest and awareness about the prospect of the TVET programme should be nurtured, especially among non-Bumiputeras, by the relevant parties such as government, teachers, parents, and the community so as to enhance students’ participation in the TVET programme.